Grain boundary sliding, triple junction disclinations and strain hardening in ultrafine-grained and nanocrystalline metals. (September 2017) - Ovid'ko, I.A.; Sheinerman, A.G.
Abstract: A theoretical model is suggested which describes grain boundary (GB) sliding and its accommodation through dislocation slip in ultrafine-grained and nanocrystalline metals. The initial stage of the accommodating dislocation slip represents emission of lattice dislocations from triple junctions into grain interiors. The lattice dislocations emitted from a triple junction slip across a grain and are absorbed by an opposite GB where they are dissociated into GB dislocations that climb along the GB. In the situation where these GB sliding and accommodating processes are dominant, stress-strain dependences are calculated in ultrafine-grained copper. With the calculated dependences, we found that pronounced strain hardening occurs which is related to the accommodation processes and associated formation of disclinations at triple junctions of GBs. It is theoretically revealed that the special (new) strain hardening mechanism under discussion can play a significant role in enhancing ductility of ultrafine-grained and nanocrystalline metals at comparatively low temperatures. Highlights: A model for grain boundary (GB) sliding and its accommodation is proposed. GB sliding is accommodated via lattice dislocation emission from triple junctions. Absorption of emitted lattice dislocations by GBs provides high strain hardening. Strain hardening enhances ductility of nanomaterials at low temperatures.